PENGGUNAAN QUIZALIZE SEBAGAI MEDIA PEMBELAJARAN DIGITAL BERBASIS GAME DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Faiza Zalfa Hafizha, Kana Febriani, Oktaviani, Primanita Sholihah Rosmana, Sofyan Iskandar, Tegar Se (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
With the development of the age and era of globalization characterized by rapid development and use of information technology, the concept of implementing learning has shifted to efforts to achieve modern learning. Modern learning is characterized by teaching materials that use digital media. Digital media is an important learning component. Since the educational process now uses highly developed digital technology in the world of education, technology is being used to advantage in improving educational services and quality. Interaction between teachers and learners needs to occur in the learning process, especially when teaching ongoing learning content. For this reason, learning media are needed so that the transmission of material from teachers to students is more interesting and optimal. Based on this, researchers hope to help teachers make learning media interesting and effective. The purpose of this work is to be able to identify and describe, depending on the task, how to use digital media to display learning through games, student activities using digital media to display learning and educational processes. That's it. Accounting for student learning outcomes using digital learning media. This type of study is a qualitative descriptive study in which all obtained data are presented orally. The main subjects of this study are 5th grade students of SDN Pucung III. Researchers create game-based digital media for 5th grade learning and analyze student activity and learning outcomes after using the media. The results of the research's analysis show that the use of digital media in learning has a significant impact on the activation of student activity during learning and the completeness of learning outcomes. It is also evident from her 5th grade percentage at Pucung III Public Elementary School. At this grade level, learning with digital media is much better than before using digital media.